All‐Optical and Label‐Free Stimulation of Action Potentials in Neurons and Cardiomyocytes by Plasmonic Porous Metamaterials. Issue 21 (5th September 2021) - Bruno, Giulia; Melle, Giovanni; Barbaglia, Andrea; Iachetta, Giuseppina; Melikov, Rustamzhon; Perrone, Michela; Dipalo, Michele; De Angelis, Francesco
Abstract: Optical stimulation technologies are gaining great consideration in cardiology, neuroscience studies, and drug discovery pathways by providing control over cell activity with high spatio‐temporal resolution. However, this high precision requires manipulation of biological processes at genetic level concealing its development from broad scale application. Therefore, translating these technologies into tools for medical or pharmacological applications remains a challenge. Here, an all‐optical nongenetic method for the modulation of electrogenic cells is introduced. It is demonstrated that plasmonic metamaterials can be used to elicit action potentials by converting near infrared laser pulses into stimulatory currents. The suggested approach allows for the stimulation of cardiomyocytes and neurons directly on commercial complementary metal‐oxide semiconductor microelectrode arrays coupled with ultrafast pulsed laser, providing both stimulation and network‐level recordings on the same device. Abstract : The complementary metal‐oxide semiconductor (CMOS) multi‐electrode array coupled with picosecond near infrared laser pulses is capable of stimulating electrogenic cells. When irradiated, the plasmonic material covering the CMOS microelectrode arrays (MEAs) electrodes produces nanoampere currents due to the hot electron injection in the cleft. This can specifically elicit cardiomyocytes and neuronal cells directly in situ without genetic or thermal tools.